MITOS CANTIK PADA IKLAN PERAWATAN KULIT LANEIGE - Siti Novita Anindita, Rah Utami Nugrahani (Universitas Informatika dan Bisnis Indonesia, 2018)
Beauty is identical with women. Beautiful has many versions depending on several factors, point of view, until the area. Laneige skincare advertisement shows signs and symbols that indicate a beautiful element. This ad uses YouTube social media which is new media. YouTube has audio-visual features and YouTube is the most popular online video community in the world. The author wants to see the beautiful myths that existed in the Laneige skin-care ad version of